2021
DOI: 10.1111/hsc.13365
|View full text |Cite
|
Sign up to set email alerts
|

Colliding worlds: Family carers’ experiences of balancing work and care in Ireland during the COVID‐19 pandemic

Abstract: The Coronavirus disease 2019 (COVID-19) pandemic public health and social protective measures imposed globally resulted in partial or full closure of key services and supports for services and supports for people with a disability, chronic illness or age-related dependency. This caused huge disruption to care provision and family carers were relied upon to assume this care at home. Many family carers, including those in employment, found themselves navigating additional care responsibilities without 'usual lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 33 publications
9
38
0
Order By: Relevance
“…The most analysed perspective in the literature on the work-family relationship has been the negative one, whose core concept is work-family conflict. In their study, Greenhaus and Beutell [4] highlight three types of conflict or relationship; transposing it to this research, they identified the following: (i) the first, temporal-based, arises from the time required to perform one role interfering with the time available to perform another, reducing said role [46,93,94]; (ii) the second refers to pressure conflicts and is based on the conception that the pressure caused in one domain will affect the other domain [35,41,44] and, (iii) the third refers to the type of behavioral conflict that concerns the incompatibility of behaviors expected in each of the roles [33,39,43].…”
Section: Discussionmentioning
confidence: 99%
“…The most analysed perspective in the literature on the work-family relationship has been the negative one, whose core concept is work-family conflict. In their study, Greenhaus and Beutell [4] highlight three types of conflict or relationship; transposing it to this research, they identified the following: (i) the first, temporal-based, arises from the time required to perform one role interfering with the time available to perform another, reducing said role [46,93,94]; (ii) the second refers to pressure conflicts and is based on the conception that the pressure caused in one domain will affect the other domain [35,41,44] and, (iii) the third refers to the type of behavioral conflict that concerns the incompatibility of behaviors expected in each of the roles [33,39,43].…”
Section: Discussionmentioning
confidence: 99%
“…This is echoed in our study, which showed that the percentage of those struggling with mental health increased from 61% to 76% for those with carers. Almost half of the respondents who required regular support or personal assistance at home had their hours either completely or partially reduced, which can create challenges at home with signi cant stress for the primary carers (24).…”
Section: Discussionmentioning
confidence: 99%
“…Social/physical distancing orders and loss of external support for their care-recipient has meant that many carers have been singularly providing care without respite or breaks, and often in the form of emotional support, leaving them vulnerable to poorer mental health (Embracing Carers 2020; Mata et al 2020;Lafferty et al 2021). At the same time, since many carers are working remotely from their own homes, they have seen their own homecare responsibilities increase and compound with work and caring obligations, as their work and home worlds collide and integrate in previously unforeseen ways.…”
Section: Covid-19mentioning
confidence: 99%
“…Of 755 Canadian carers surveyed, 70% reported worsening emotional and mental health during the pandemic, with average weekly time spent caring increasing 28% to 21.6 hours per week at the time of Canada's second wave of cases (fall 2020), compared to the pre‐pandemic baseline (Embracing Carers 2020 ). Social/physical distancing orders and loss of external support for their care‐recipient has meant that many carers have been singularly providing care without respite or breaks, and often in the form of emotional support, leaving them vulnerable to poorer mental health (Embracing Carers 2020 ; Mata et al 2020 ; Lafferty et al 2021 ). At the same time, since many carers are working remotely from their own homes, they have seen their own homecare responsibilities increase and compound with work and caring obligations, as their work and home worlds collide and integrate in previously unforeseen ways.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation